Odd women? : spinsters, lesbians and widows in British women's fiction, 1850s-1930s - Liggins, Emma (Manchester University Press, 2014)
Women outside marriage between 1850 and the Second World War were seen as abnormal, threatening, superfluous and incomplete, whilst also being hailed as 'women of the future'. Before 1850 odd women were marginalised, minor characters, yet by the 1930s spinsters, lesbians and widows had become heroines. This book considers how Victorian and modernist women's writing challenged the heterosexual plot and reconfigured conceptualisations of public and private space in order to valorise female oddity.